The Perception of Pathumthani Residents Toward Its Environmental Quality, Suburban Area of Thailand - Iamtrakul, Pawinee; Chayphong, Sararad (Geographica Pannonica, 2021)
The urbanization process is often concentrated mostly in urban areas, resulting into urban development sprawl. This has effects on the lifestyles and activities of urban people, which in turn significantly affects the health of the city. The quality of the urban environment plays an important role in public health with respect to urban issues ranging from quality of utilities and services to quality of life. This study aims to study the perception of Pathumthani residents toward its environmental quality through spatial cluster analysis. A total of 1,000 sets of data collected from the interview survey among residents or commuters traveling through Pathumthani province was used for this study. The residents’ response towards environmental factors was examined through the classification of their different opinions among built environment and health aspects. The statistical analysis which was performed in this study was cluster analysis to demonstrate its relationship. With the level of satisfaction on environment aspect and health status in indicating number of congenital diseases, the result of this study found that condition of living environment (through Likert scale) affects the urban health with statistical significance of (P <0.05). Therefore, provincial health policy should focus more on developing a healthy city in consistence with economic and social development while putting adequate mechanisms for environmental surveillance monitoring at the community level. The result of study can confirm the usefulness of this unconventional approach by asking residents or commuters about their satisfaction on built environment which can represent as an evidence-based planning approach by linking local people attitudes and translating them into creating liveable and better urban environmental quality. To have a good understanding of local people preferences, the recommendation to be given to the capacity of communities can be focused for improving people’s quality of life by providing better accessibility, high quality of infrastructures and services. Finally, a set of features of satisfied built environment can help to support the continued growth of the city in term of basic need and sufficiency provision of facility and utility system.